PREPARING THE YOUNGER GENERATION TO BECOME ENVIRONMENTAL HEALTH AMBASSADORS - Loso Judijanto; Entin Solihah (ZAHRA: JOURNAL OF HEALTH AND MEDICAL RESEARCH, 2026)
This article discusses the importance of preparing young people as environmental health ambassadors through education and active involvement in activities that support environmental sustainability. Formal education in schools serves as the main foundation in raising environmental awareness, while the role of community and family strengthens the application of environmental values in daily life. In addition, support from the government and non-governmental organisations (NGOs) through training programmes and campaigns is crucial to provide a platform that enables the younger generation to contribute to environmental conservation. With a comprehensive and synergistic strategy, young people can be empowered to become agents of change dedicated to maintaining and improving environmental health.